LccA, an Archaeal Laccase Secreted as a Highly Stable Glycoprotein into the Extracellular Medium by Haloferax volcanii - Uthandi, Sivakumar (American Society for Microbiology (ASM), 2010)
Laccases couple the oxidation of phenolic compounds to the reduction of molecular oxygen and thus span a wide variety of applications. While laccases of eukaryotes and bacteria are well characterized, these enzymes have not been described in archaea. Here, we report the purification and characterization of a laccase (LccA) from the halophilic archaeon Haloferax volcanii. LccA was secreted at high levels into the culture supernatant of a recombinant H. volcanii strain, with peak activity (170 ± 10 mU·ml(−)(1)) at stationary phase (72 to 80 h). LccA was purified 13-fold to an overall yield of 72% and a specific activity of 29.4 U·mg(−)(1) with an absorbance spectrum typical of blue multicopper oxidases. The mature LccA was processed to expose an N-terminal Ala after the removal of 31 amino acid residues and was glycosylated to 6.9% carbohydrate content. Purified LccA oxidized a variety of organic substrates, including bilirubin, syringaldazine (SGZ), 2,2,-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), and dimethoxyphenol (DMP), with DMP oxidation requiring the addition of CuSO(4). Optimal oxidation of ABTS and SGZ was at 45°C and pH 6 and pH 8.4, respectively. The apparent K(m) values for SGZ, bilirubin, and ABTS were 35, 236, and 670 μM, with corresponding k(cat) values of 22, 29, and 10 s(−)(1), respectively. The purified LccA was tolerant of high salt, mixed organosolvents, and high temperatures, with a half-life of inactivation at 50°C of 31.5 h.